Endoscopic necrosectomy of infected WON in acute necrotising pancreatitis – Development of an effective therapeutic algorithm based on a single-center consecutive patient cohort - Jaeger, Kristin; Meyer, Frank; Füldner, Frank; Will, Uwe (Zeitschrift für Gastroenterologie, 2022)
Objective Development of an effective therapeutic algorithm for interventional (minimally invasive) approach to infected walled-off necrosis (WON) in patients with necrotising pancreatitis reflecting real-word data.Material/methods All consecutive patients who underwent endoscopic necrosectomy for necrotising pancreatitis through a defined study period were enclosed in this retrospective observational case study. The therapeutic approach was analysed for clinical success rate, complication spectrum and rate as well as mortality and compared with data from the literature. Finally, a therapeutic algorithm was derived.Results From 2004 to 2019, 126 patients with necrotising pancreatitis (median of APACHE II score, 10.5 points) were treated. In 92.9 % of cases (n=117), an infected WON with microbial pathogen detection was found. After a median of 18 days from symptom onset, first intervention was performed (53.2 % as percutaneous drainage with programmed rinsing, 29.4 % as EUS-guided internal drainage). From 2004 to 2010, double pigtail stents were used. Later, lumen-apposing metal stent (LAMS) such as AXIOSTM stent (Boston Scientific, Ratingen, Germany) was preferred. The combined percutaneous and internal drainage was performed in approximately 50 % of subjects.Endoscopic transluminal necrosectomy was performed in 123 patients (97.6 %) at a median of 33 days from symptom onset. Endoscopic percutaneous necrosectomy was conducted in 11.1 % of the individuals. A median number of two endoscopic necrosectomy sessions per patient was necessary for the therapy. The clinical success rate (discharge without surgical intervention) was 82.5 %. The complication rate (bleeding and perforation) and the need for surgery were both 9.5 %. The overall mortality was 8.7 %.Conclusion Therapy of necrotising pancreatitis with infected WON consists of early calculated antibiotic therapy with adequate drainage. Combined external and internal drainages with programmed rinsing seem to improve prognosis, as well as minimise i) the need for forced necrosectomies (mainly via a transluminal access site) and ii) complication rate as well as, thus, improve outcome.
Keywords: akute (nekrotisierende) Pankreatitis; (infizierte) Walled-off necroses (WON); endoskopische Nekrosektomie; therapeutischer Algorithmus